1991
DOI: 10.1104/pp.96.4.1167
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Oligogalacturonides Activate the Oxidation of Indoleacetic Acid by Peroxidase

Abstract: Partial hydrolysis of polygalacturonic acid with a purified a-1,4-endopolygalacturonase yielded oligogalacturonides and trace amounts of a series of modified oligogalacturonides. Three of the minor products were isolated and identified as oxidized oligogalacturonides possessing termini of galactaric acid. Oxidation of indole-3-acetic acid by peroxidases was activated by oxidized oligogalacturonides but not by normal analogs.Oligosaccharides composed of 1,4-linked a-D-galacturonic acid residues (oligogalacturon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Threonic acid and glyceric acid have been reported to be sensitive to heat stress in many species, including arabidopsis (Kaplan et al, 2004), hybrid bermudagrass, and kentucky bluegrass (Du et al, 2011). Galactaric acid is derived from galacturonic acid by galacturonic acid oxidase, which has been found to stimulate the oxidation of indole acetic acid by peroxidase (Pressey, 1991) and acts as a substrate for galacturonic acid reductase leading to the synthesis of ascorbic acid. Sanchez et al (2008) reported that galactaric acid was decreased by salinity in arabidopsis.…”
Section: Resultsmentioning
confidence: 99%
“…Threonic acid and glyceric acid have been reported to be sensitive to heat stress in many species, including arabidopsis (Kaplan et al, 2004), hybrid bermudagrass, and kentucky bluegrass (Du et al, 2011). Galactaric acid is derived from galacturonic acid by galacturonic acid oxidase, which has been found to stimulate the oxidation of indole acetic acid by peroxidase (Pressey, 1991) and acts as a substrate for galacturonic acid reductase leading to the synthesis of ascorbic acid. Sanchez et al (2008) reported that galactaric acid was decreased by salinity in arabidopsis.…”
Section: Resultsmentioning
confidence: 99%
“…In B. cinerea-infected leaves, most PG products were converted into GalA 3 Me and GalA 2 ox. The production of the latter OGs presumably involved plant-produced OG oxidases (OGOX) (17,34,35) of the berberine bridge enzyme family. Oxidized OGs are more recalcitrant to the hydrolysis of fungal enzymes and, interestingly, plants overexpressing OGOX1 are more resistant to B. cinerea.…”
Section: Discussionmentioning
confidence: 99%
“…TCLs will form roots, flowers, or vegetative shoots, depending on the auxin/cytokinin ratio (Mohnen et al, 1990). Oligogalacturonides can induce flower formation or inhibit root formation in tobacco TCLs or leaf explants (Eberhard et al, 1989;Mohnen et al, 1990;MarFa et al, 1991); they may act by interfering with auxin binding sites (LoSchiavo et al, 1991;Filippini et al, 1992) or by altering auxin metabolism (Pressey, 1991). However, little is known about the role of these pectic oligosaccharins in whole plant growth and development.…”
Section: Pectic Oligosaccharinsmentioning
confidence: 99%